2023
DOI: 10.3390/molecules28052039
|View full text |Cite
|
Sign up to set email alerts
|

Determination of β2-Agonist Residues in Fermented Ham Using UHPLC-MS/MS after Enzymatic Digestion and Sulfonic Resin Solid Phase Purification

Abstract: β2-agonists are a class of synthetic sympathomimetic drugs with acute poisoning effects if consumed as residues in foods. To improve the efficiency of sample preparation and to overcome matrix-dependent signal suppression in the quantitative analysis of four β2-agonists (clenbuterol, ractopamine, salbutamol, and terbutaline) residues in fermented ham, an enzyme digestion coupled cation exchange purification method for sample preparation was established using ultra-high performance liquid chromatography and tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The present study indicated that the transfer rate differed among the three β‐agonists, which might be a consequence of the fermentation process used in the manufacturing of the medium. As reported, β‐agonists can be biodegraded to other complex and undetermined chemicals by microorganisms and enzymes during fermentation [38]. There were differences in the biodegradation rate of the three β‐agonists over 20 days following drying, moistening, crushing, piling, and fermenting twice.…”
Section: Discussionmentioning
confidence: 81%
“…The present study indicated that the transfer rate differed among the three β‐agonists, which might be a consequence of the fermentation process used in the manufacturing of the medium. As reported, β‐agonists can be biodegraded to other complex and undetermined chemicals by microorganisms and enzymes during fermentation [38]. There were differences in the biodegradation rate of the three β‐agonists over 20 days following drying, moistening, crushing, piling, and fermenting twice.…”
Section: Discussionmentioning
confidence: 81%
“…The method was compared with other methods in the literature, comparing the parameters (Table 2). Considering enzymatic hydrolysis methods SPE-UHPLC-MS/MS [7], MCXSPE-LC-MS/MS [34], micro-extraction-UHPLC-Q ExactiveTM Plus Orbitrap MS [35], and MMIPSPE-HPLC [36], the LOD and recovery of the current SPE-GC-MS method based on the ZMS@N-CQDs are comparable, but the pre-treatment procedure of other methods is relatively complex and the linear range is relatively narrow, which is not suitable for rapid, wide spectrum detection. Therefore, the current developed method is a simple, sensitive, and wide-spectrum method for the analysis of β 2 -agonist residues in meat.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…However, it has been verified that acute intoxication, including headache, tachycardia nausea, dizziness, and other symptoms, may occur when people eat meats made from animals fed by β 2 -agonists; therefore, the use of these kinds of stimulants was banned by the World Health Organization (WHO) and many countries [4][5][6]. Meanwhile, in recent years, the abuse of these compounds has formed severe food safety risks [7]. Even if the concentration is extremely low in animal products, β 2 -agonists will still pose potential and substantial threats to the health of humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, analytical methods for detecting Rac in pork are limited to techniques requiring highly sophisticated sample preparation or costly instrumentation, such as enzyme-linked immunosorbent assay (ELISA), high-performance liquid chromatography (HPLC), gas chromatography–mass spectrometry (GC–MS), and liquid chromatography–tandem mass spectrometry (LC–MS/MS). ELISA offers a rapid and portable method for detecting Rac; however, its major drawback is its requirements of complicated time-consuming sample pretreatment and preparation because of the complex matrix of animal tissues . Among instrumental techniques, HPLC enables multicomponent and highly sensitive analysis; however, the HPLC instrument is costly and nonportable, which prevents its widespread application .…”
Section: Introductionmentioning
confidence: 99%